Developing the archaebacteria and eubacteria web-based learning media for high school students - Hidayah, Maulida Ulfa; Lumowa, Sonja V. T.; Boleng, Didimus Tanah (Jurnal Pendidikan Biologi Indonesia, 2018)
The 21st-century biology learning requires technology-based learning which is potential in improving studentsâ learning outcomes. This research aimed to examine the validity and effectiveness of web-based learning media on Archaebacteria and Eubacteria on learning process. This web-based learning media was structured by using 4-D Thiagarajan model. The research was conducted at three SSHSs of Samarinda. The data were obtained from validatorsâ (media expert, material expert, and linguist), teachersâ, and studentsâ opinion by using questionnaire; while the effectiveness was determined based on studentsâ test score and their response. The results showed that the web-based learning media was very valid with the average score from experts as high as 95.27%. Moreover, this media has been proven to improve the studentâs cognitive learning outcomes (gain score 0.39) and well responded by both teachers and students. Â